Coexistent chlamydial infections related to natural history of human papillomavirus lesions in uterine cervix. - Syrjänen, K (1986)
To assess the role of Chlamydia trachomatis in the development of cervical intraepithelial neoplasia (CIN) and to evaluate possible synergism between chlamydiae and human papillomavirus (HPV) in this process, 418 women who had been prospectively followed up for cervical HPV infections at our clinic since 1981 were tested for chlamydiae. At each visit the patients were examined by colposcopy, and other investigations, such as Papanicolaou (Pap) smears, punch biopsies, urethral, and cervical swabs, were undertaken as indicated. In biopsy specimens the cytopathic changes of HPV, concomitant CIN, and the local immunocompetent cell infiltrates were analysed. The latter were measured and further identified using an alpha naphthyl acetate esterase (ANAE) technique to define B cells, macrophages, and T cells and using monoclonal antibodies to define T cell subsets, NK (natural killer cells), and Langerhans cells. Chlamydial isolation (4.1% in the cervix, and 3.6% in the urethra) did not positively correlate with the degree of cytological atypia in PAP smears or with the degree of CIN lesions associated with HPV. Chlamydial cervicitis did not affect the ANAE definable cell composition of the immunocompetent cell infiltrates in HPV lesions, or that of the immunocompetent cell subsets, including the ratios of T helper to T suppressor cells and the numbers of NK cells. Chlamydial infection did not alter the natural history of HPV lesions, of which 30% regressed, 53% persisted, and 17% progressed during follow up. The present results do not provide evidence to substantiate the hypothesis that chlamydiae and HPV might act synergistically in cervical carcinogenesis, or the view that C trachomatis may be a major aetiological agent of CIN lesions. Chlamydiae and HPV are covariables of sexual behaviour, and their concomitant appearance in sexually promiscuous women is best explained by this fact. As we do not have more direct evidence for the oncogenic potential of C trachomatis (as we have of HPV), it seems reasonable to consider that this agent is not a major cause of CIN, but rather a sexually transmitted agent commonly found in women with CIN because of their promiscuous sexual behaviour.